2016
DOI: 10.15713/ins.jcri.109
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and awareness of temporomandibular joint disorders among general dental practitioners in Southern India

Abstract: Aim:To evaluate the awareness of diagnosis and management of temporomandibular disorders (TMDs) among general dental practitioners and to understand their attitude toward the relevance of these disorders. Materials and Methods: A questionnaire containing 17 questions regarding etiology, signs and symptoms, investigations and management of temporomandibular joint disorders and about the relevance of managing the same in routine clinical practice was answered by 100 general dental practitioners in Southern India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The awareness about multidisciplinary approach may help health practitioners to refer TMD patients to other specialists for better management of the condition [35], and much better prognosis can be achieved by dentist and PTs collaboration [7]. Up to the authors' knowledge, no studies were done in neither the SA nor other Arab countries to assess the awareness about PT role among dentists.…”
Section: Introductionmentioning
confidence: 98%
“…The awareness about multidisciplinary approach may help health practitioners to refer TMD patients to other specialists for better management of the condition [35], and much better prognosis can be achieved by dentist and PTs collaboration [7]. Up to the authors' knowledge, no studies were done in neither the SA nor other Arab countries to assess the awareness about PT role among dentists.…”
Section: Introductionmentioning
confidence: 98%
“…The study concluded that general dental practitioners could benefit from education programs aimed at highlighting the management aspect of TMD. [28] Another study done in Lahore found that 65% dentists did not consider physiotherapy as a treatment option for TMD, while 27% considered that it may be a treatment option and only 8% considered it as a treatment option. Treatment choice of most dentists was using a combination of medications and precautions (64%) while only 7% of dentists referred people with TMD for physiotherapy.…”
Section: Introductionmentioning
confidence: 99%